No differences in executive functions between female and male young talented football players - Lehmann, J.; Pietsch, S. (Frontiers in Psychology, 2025)
Introduction: Research regarding the relationship between cognitive performance and sport performance in young talented football players has mainly been investigated in male athletes. Only few studies have addressed these aspects in female athletes. Thus, this quasi-experimental cross-sectional study aims to contribute to research addressing possible sex differences in the relationship of cognitive aspects in young talented football players during a selection assessment for a representative team and possible adjustments in this process or training processes in consideration of potential sex differences.